Preliminary investigation on the mechanical properties of carboxylated nitrile butadiene rubber (XNBR) blended with different loadings of butyl reclaimed rubber (BRR) /Zafirah Zainal Abidin ... [et al.] - Zainal Abidin, Zafirah; Mamauod, Siti Nur Liyana; Sarkawi, Siti Salina; Mamauod, Muhammad Ilham; Dareen Khooi, Dareen Khooi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2024)
Reclaimed rubber (RR) from butyl tubes was evaluated as a partial and full replacement of a virgin rubber which is carboxylated nitrile butadiene (XNBR). This study involves the blending of carboxylated nitrile butadiene rubber with butyl reclaimed rubber (XNBR/BRR) in various loadings and cured with sulfur by using a two-roll mill. The objective is to investigate the effect of RR loading on crosslink density and mechanical properties of XNBR/BRR blends. The mechanical properties such as hardness, rebound resilience, tear strength, tensile strength, elongation at break, and modulus were evaluated. In this study, the amount of reclaimed rubber varied from 0 phr to 161 phr. The results showed that the rebound resilience, tear strength, and tensile strength had a reduction of 43%, 27%, and 67%, respectively. Also, the hardness and modulus increased by 17% and 60% each. As for the elongation at break, it had a decrease of 69% and then an increment of about 77%. These results appeared due to the low molecular 1 weight of the BRR800 and the presence of processing oil and carbon black in the reclaimed rubber itself. This study could prove that reclaimed rubber can be fully utilized by putting it to good use in producing good quality rubber-based products.